Business data processing based on algebra-logical models - Cherednichenko, Olga Yurevna; Gontar, Yulia Mukolaivna; Vasylenko, Artem Viktorovich; Matvieiev, O. (Харківський національний університет Повітряних Сил ім. Івана Кожедуба, 2017)
Issues of business information processing, which are necessary for management decision- making, are considered in the article. Algebraic-logical models, which allows to process heterogeneous information obtained from various sources are presented. In the case study the reference model of business information processing on the stage of project plan elaboration is presented. Correspondence between an artifact and associated with it requirement is performed by comparator identification.

У статті розглянуті питання обробки інформації, необхідної для прийняття управлінських рішень. Представлені алгебро-логічні моделі, які дозволяють обробляти неоднорідну інформацію, отриману з різних джерел. У практичному прикладі представлена еталонна модель обробки ділової інформації, отриманої зі сховищ підприємства, на етапі розробки плану проекту. Відповідність артефакта вимогам здійснюється за допомогою компараторної ідентифікації.
Обробка бізнес-інформації на основі алгебро-логічних моделей
Keywords: business data processing; model; decision making; predicates algebra; comparator identification; обробка бізнес-інформації; модель; прийняття рішень; алгебра предикатів; компараторна ідентифікація